The Civilizing Education: Study of Ibn Khaldun's Educational Thinking for Society 5.0 Era - Suwartini, Sri; Sutrisno, Sutrisno; Prastowo, Andi (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2022)
Abstract Education in Society 5.0 Era is essential to make a significant contribution to the development of a morally advanced society. Through Ibn Khaldun's perspective, this essay aimed to find relevant educational theories and models for contemporary society. His selection was based on his renown in the disciplines of social and political philosophy and education. First the results of the study identified three essential components for the development of the ideal civilization: asabiyyah, science and technology, and attitudes toward luxury. Therefore, from Ibn Khaldun's point of view, the perfect education should foster the growth of these three crucial elements. Second, this study presented the Civilizing Education model that put an emphasis on citizenship, cooperation, specialization of expertise, morality, sufism, and anti-corruption. When compared to philosophical groundwork of multicultural education which is currently used in the framework of Society 5.0, the Civilizing Education model is quiet compatible. Researchers and educational professionals interested in creating a multicultural education model based on the perspectives of ancient Muslim thinkers should read this paper. AbstrakPendidikan di Era Masyarakat 5.0 sangat penting untuk memberikan kontribusi yang signifikan bagi pengembangan masyarakat yang maju secara moral. Melalui perspektif Ibn Khaldun, esai ini bertujuan untuk menemukan teori dan model pendidikan yang relevan bagi masyarakat kontemporer. Pemilihannya didasarkan pada ketenarannya dalam disiplin filsafat dan pendidikan sosial dan politik. Pertama, hasil penelitian mengidentifikasi tiga komponen penting untuk pengembangan peradaban ideal: asabiyyah, sains dan teknologi, dan sikap terhadap kemewahan. Oleh karena itu, dari sudut pandang Ibnu Khaldun, pendidikan yang sempurna harus mendorong tumbuhnya ketiga unsur penting tersebut. Kedua, penelitian ini mempresentasikan model Civilization Education yang menitikberatkan pada kewarganegaraan, kerjasama, spesialisasi keahlian, moralitas, tasawuf, dan antikorupsi. Jika dibandingkan dengan landasan filosofis pendidikan multikultural yang saat ini digunakan dalam kerangka Society 5.0, model Civilization Education cukup kompatibel. Para peneliti dan profesional pendidikan yang tertarik untuk menciptakan model pendidikan multikultural berdasarkan perspektif pemikir Muslim kuno harus membaca makalah ini.How to Cite: Suwartini, S., Sutrisno, Prastowo, A. (2022). The Civilizing Education: Study of Ibn Khaldun's Educational Thinking for Society 5.0 Era . TARBIYA: Journal of Education in Muslim Society, 9(2), 35-50. doi:10.15408/tjems.v9i1. 26357.